Analisis Validitas Instrument Self-Efficacy Belajar Siswa Pada Sekolah Terbuka Atlet Dengan Menggunakan Model Rasch - Haifa Munajjah, Siti Najmi; Supriatna, Mamat; Suryana, Dodi (JKI (Jurnal Konseling Indonesia), 2023)
Self-Efficacy is an individual's belief in his own ability and competence to carry out his duties or activities which is demonstrated by the individual's way of acting and overcoming existing obstacles to succeed in achieving various goals. This research aims to test the validity and reliability of students' learning self-efficacy instruments using the Rasch model. The subjects of this research were students who took part in the athlete's open school program. The method used is a cross-sectional survey with a quantitative approach. The number of participants used was 69 students at one of the State High Schools in Bandung City, West Java, Indonesia with an age range of 15-17 years. Data analysis using the Rasch model in the WinStep 3.73 application. The results of the analysis show that the respondent's interaction with the items is in the good category. The respondent's reliability value, which shows the respondent's consistency in filling out the instrument, is included in the sufficient category. The reliability of the instrument shows that it is in the very good category. The unidimensional value is included in the sufficient category. Apart from that, there are three items that are not appropriate. It is hoped that with the results of this research, instruments for measuring students' learning self-efficacy can be evaluated and developed so that an accurate instrument can be obtained in measuring students' learning self-efficacy